A Mixed Method Review of Tobacco Cessation for the Cardiopulmonary Rehabilitation Clinician. Issue 3 (May 2017) - Mola, Ana; Lloyd, Madeleine M.; Villegas-Pantoja, Miguel A.
Abstract : PURPOSE: To systematically survey the literature, describe the current tobacco science, and perform a mixed method review of randomized control trials of tobacco research in the cardiopulmonary population. METHODS: Mixed method review was conducted on major resource databases. Inclusion criteria were English language with a minimum follow-up of 6 months, published between January 1, 2007, and June 30, 2016; adult smokers ≥18 years of age with cardiovascular and/or pulmonary disease; initiation of subject recruitment from hospital or community; tobacco cessation (TC) as the main aim of the study; biometric validation of smoking status; first-line TC medications; and nonpharmacological treatments. RESULTS: The pooling of the 10 studies through forest plot analysis revealed the effect of tobacco continuous abstinence rates significant at 3, 6, and 12 months (total OR = 3.73; 95% CI, 2.58-5.38). Also, tobacco point prevalence rates of TC treatments demonstrated overall effects that were significant at the different end points (total OR = 2.63; 95% CI, 1.90-3.64). In both cases, the higher ORs were found in the 3 months end point. Most successful interventions consisted of a combination of pharmacological and nonpharmacological therapy (predominantly counseling). CONCLUSIONS: The evidence continues to support the recommended first-line TC pharmacotherapy and nonpharmacological practices published in the 2008 national guidelines. Implications for cardiopulmonary rehabilitation clinicians are discussed. Abstract : The current tobacco science and a mixed method review of tobacco cessation research in the cardiopulmonary population supports the 2008 national guidelines first-line cessation practices. Implications for cardiopulmonary rehabilitation clinicians are discussed.